Blockchain application in hospitals to digitalize healthcare services : designing a distributed electronic health record ecosystem in Vietnamese public hospitals - Hoang Van Tho; Badir, Yousre F. M.; Mongkol Ekpanyapong; Junaid, Muhammad (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
This research investigates how blockchain technology can be applied to design a distributed Electronic Health Record (EHR) ecosystem tailored to the context of Vietnamese public hospitals. Amid rising demands for digital transformation in Vietnam's healthcare system, traditional EHR systems have struggled with fragmentation, limited interoperability, weak patient control, and data privacy concerns. To address these issues, this study adopts an action research methodology and develops two in-depth case studies at Hospital-A in Hanoi and Hospital-B in Ho Chi Minh City, two of Vietnam{u2019}s leading national referral hospitals. The study presents a comprehensive analysis across seven dimensions: institutional background, organizational governance, clinical services, academic and research role, digitalization strategies, blockchain-based EHR design, and summary insights. Both hospitals have implemented pilot blockchain systems using Hyperledger Fabric, integrating smart contracts, IPFS storage, and VNeID-based patient authentication. The research highlights key findings regarding system interoperability, trust enhancement, and the role of smart contracts in access control and consent management. Through qualitative data from interviews, focus groups, and technical implementation reports, the study identifies critical enablers and barriers to blockchain adoption in the Vietnamese healthcare environment. These include technical capacity, hospital leadership, regulatory readiness, and inter-hospital collaboration. By evaluating the technical architecture, performance, and implementation process in two contrasting urban settings, the research offers a framework for scalable, secure, and patient-centered digital health transformation. It concludes with policy recommendations, a roadmap for national EHR interoperability, and implications for blockchain adoption in other low- and middle-income healthcare systems.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Business Administration
Thesis (Ph.D.) - Asian Institute of Technology, 2025
Keywords: Medical records -- Data processing -- Vietnam; Electronic Health Record -- Vietnam; Hospitals -- Technological innovations -- Vietnam; Blockchains (Databases)